West African masking traditions and diaspora masquerade carnivals : history, memory, and transnationalism - Njoku, Raphael Chijioke (Rochester studies in African history and the diaspora, 2020)
"A revisionist account of African masquerade carnivals in transnational context that offers readers a unique perspective on the connecting threads between African cultural trends and African American cultural artifacts"--